Impact of Interfacing Near Point of Care Clinical Chemistry and Hematology Analyzers at Urgent Care Clinics at an Academic Health System - Zachary J. Fleishhacker; Prerna Rastogi; Scott R. Davis; Dean R. Aman; Cory S. Morris; Richard L. Dyson; Matthew D. Krasowski (Elsevier, 2022)
Background: Point-of-care (POC) testing equipment is commonly utilized in outpatient clinics. Our institution recently interfaced POC chemistry and hematology devices at two outpatient clinics via middleware software to the central electronic health record (EHR), facilitating a comparison of manual transcription versus automatic reporting via interface. This allowed for estimation of serious/obvious error rates and manual time savings. Additional goals were to develop autoverification rules and analyze broad trends of results in response to common clinician complaints on the POC testing. Material and Methods: Data were obtained from two satellite clinic sites providing both primary and urgent care within an academic health system. Interface of devices was accomplished via Instrument Manager middleware software and occurred approximately halfway through the 38 month retrospective timeframe. Laboratory results for three testing POC chemistry and hematology panels were extracted with EHR tools. Results: Nearly 100,000 lab values were analyzed and revealed that the rate of laboratory values outside reference range was essentially unchanged before and after interface of POC testing devices (2.0-2.1%). Serious/obvious errors, while rare overall, declined significantly, with none recorded after the interface with autoverified results and only three related to manual edits of results that failed autoverification. Fewer duplicated test results were identified after the interface, most notably with the hematology testing. Anion gap values of less than zero were observed more frequently in POC device tests when compared to central laboratory tests and are attributed to a higher proportion of Cl values greater than 110 mEq/L and CO2 values greater than 30 mEq/L with POC results. Time savings of eliminating manual data entry were calculated to be 21.6 employee hours per month. Conclusions: In a switch from manual entry to automatic interface for POC chemistry and hematology, the most notable changes were reduction of serious/obvious errors and duplicate results. Significant time employee time savings highlight an additional benefit of instrument interfacing. Lastly, a difference between POC and central laboratory instruments is a higher rate of high Cl and CO2 values relative to the central laboratory.